The prostaglandin pathway is activated in patients who fail medical therapy for benign prostatic hyperplasia with lower urinary tract symptoms. Issue 13 (20th July 2021) - Jin, RenJie; Strand, Douglas W.; Forbes, Connor M.; Case, Thomas; Cates, Justin M. M.; Liu, Qi; Ramirez‐Solano, Marisol; Milne, Ginger L.; Sanchez, Stephanie; Wang, Zunyi Y.; Bjorling, Dale E.; Miller, Nicole L.; et al.
Abstract: Background: Little is known about how benign prostatic hyperplasia (BPH) develops and why patients respond differently to medical therapy designed to reduce lower urinary tract symptoms (LUTS). The Medical Therapy of Prostatic Symptoms (MTOPS) trial randomized men with symptoms of BPH and followed response to medical therapy for up to 6 years. Treatment with a 5 α ‐reductase inhibitor (5ARI) or an alpha‐adrenergic receptor antagonist ( α ‐blocker) reduced the risk of clinical progression, while men treated with combination therapy showed a 66% decrease in risk of progressive disease. However, medical therapies for BPH/LUTS are not effective in many patients. The reasons for nonresponse or loss of therapeutic response in the remaining patients over time are unknown. A better understanding of why patients fail to respond to medical therapy may have a major impact on developing new approaches for the medical treatment of BPH/LUTS. Prostaglandins (PG) act on G‐protein‐coupled receptors (GPCRs), where PGE2 and PGF2 elicit smooth muscle contraction. Therefore, we measured PG levels in the prostate tissue of BPH/LUTS patients to assess the possibility that this signaling pathway might explain the failure of medical therapy in BPH/LUTS patients. Method: Surgical BPH (S‐BPH) was defined as benign prostatic tissue collected from the transition zone (TZ) of patients who failed medical therapy and underwent surgical intervention to relieve LUTS. Control tissue was termed Incidental BPH (I‐BPH). I‐BPH was TZ obtained from men undergoing radical prostatectomy for low‐volume, low‐grade prostatic adenocarcinoma (PCa, Gleason score ≤ 7) confined to the peripheral zone. All TZ tissue was confirmed to be cancer‐free. S‐BPH patients divided into four subgroups: patients on α ‐blockers alone, 5ARI alone, combination therapy ( α ‐blockers plus 5ARI), or no medical therapy (none) before surgical resection. I‐BPH tissue was subgrouped by prior therapy (either on α ‐blockers or without prior medical therapy before prostatectomy). We measured prostatic tissue levels of prostaglandins (PGF2 α, PGI2, PGE2, PGD2, and TxA2 ), quantitative polymerase chain reaction levels of mRNAs encoding enzymes within the PG synthesis pathway, cellular distribution of COX1 (PTGS1) and COX2 (PTGS2), and tested the ability of PGs to contract bladder smooth muscle in an in vitro assay. Results: All PGs were significantly elevated in TZ tissues from S‐BPH patients ( n = 36) compared to I‐BPH patients ( n = 15), regardless of the treatment subgroups. In S‐BPH versus I‐BPH, mRNA for PG synthetic enzymes COX1 and COX2 were significantly elevated. In addition, mRNA for enzymes that convert the precursor PGH2 to metabolite PGs were variable: PTGIS (which generates PGI2 ) and PTGDS (PGD2 ) were significantly elevated; nonsignificant increases were observed for PTGES (PGE2 ), AKR1C3 (PGF2 α ), and TBxAS1 (TxA2 ). Within the I‐BPH group, men responding to α ‐blockers for symptoms of BPH but requiring prostatectomy for PCa did not show elevated levels of COX1, COX2, or PGs. By immunohistochemistry, COX1 was predominantly observed in the prostatic stroma while COX2 was present in scattered luminal cells of isolated prostatic glands in S‐BPH. PGE2 and PGF2 α induced contraction of bladder smooth muscle in an in vitro assay. Furthermore, using the smooth muscle assay, we demonstrated that α ‐blockers that inhibit alpha‐adrenergic receptors do not appear to inhibit PG stimulation of GPCRs in bladder muscle. Only patients who required surgery to relieve BPH/LUTS symptoms showed significantly increased tissue levels of PGs and the PG synthetic enzymes. Conclusions: Treatment of BPH/LUTS by inhibition of alpha‐adrenergic receptors with pharmaceutical α ‐blockers or inhibiting androgenesis with 5ARI may fail because of elevated paracrine signaling by prostatic PGs that can cause smooth muscle contraction. In contrast to patients who fail medical therapy for BPH/LUTS, control I‐BPH patients do not show the same evidence of elevated PG pathway signaling. Elevation of the PG pathway may explain, in part, why the risk of clinical progression in the MTOPS study was only reduced by 34% with α ‐blocker treatment.